1959
DOI: 10.1021/jf60105a009
|View full text |Cite
|
Sign up to set email alerts
|

Foodstuff Volatiles, Determination of Volatile Components of Foodstuffs. Techniques and Their Application to Studies of Irradiated Beef

Abstract: Division of Agricultural and Food Chemistry, 134th Meeting, .ICS'. Chicago, III. Paper No. 954 in series approved for publication. The views or conclusions are those of the authors. Mention of company products does not constitute endorsement of the department over others not named.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1960
1960
1994
1994

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…of volatiles for mass spectral a+~alysis. The distillation procedure followed was based on that of Merritt et al (1959), employing low-temperature high-vacuum techniques.…”
Section: Distillatio~zmentioning
confidence: 99%
“…of volatiles for mass spectral a+~alysis. The distillation procedure followed was based on that of Merritt et al (1959), employing low-temperature high-vacuum techniques.…”
Section: Distillatio~zmentioning
confidence: 99%
“…In contrast, Pearson et al (1959) found post-irradiation storage of cooked meat resulted in an improvement in flavor, which is probably related to the differences between fresh raw and cooked meat, with heating being necessary to prevent further flavor deterioration caused by the indigenous enzymes during storage of raw irradiated meat. Merritt et al (1959) were able to identify 10 compounds in the volatiles isolated from irradiated beef using a low-temperature vacuum distillation procedure. They showed that of these 10 compounds (i.e.…”
Section: Irradiation Flavor/odormentioning
confidence: 99%
“…Some proteins, such as beef protein, may yield ammonia and at least six amines, predominant among which are methylamine and ethyl amine (8). The sulfur-containing amino acids yield methyl mercaptan, hydrogen sulfide, methyl disulfide, and isobutyl mercap tan (9) . These products are odoriferous and bad tasting, which characterizes the adverse properties of some irradiated foods.…”
Section: Considerations On Effect Of Radiation On Chemical Compositiomentioning
confidence: 99%